2000
DOI: 10.1200/jco.2000.18.24.4016
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome for Patients With Nonmetastatic Osteosarcoma of the Extremity Treated at the Istituto Ortopedico Rizzoli According to the Istituto Ortopedico Rizzoli/Osteosarcoma-2 Protocol: An Updated Report

Abstract: With an aggressive neoadjuvant chemotherapy, it is possible to cure more than 60% of patients with nonmetastatic osteosarcoma of the extremity and amputation may be avoided in more than 80% of them. Because local or systemic relapses, myocardiopathies, and second malignancies are possible even 5 years or more after the beginning of treatment, a long-term follow-up is recommended for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
240
1
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 381 publications
(264 citation statements)
references
References 40 publications
11
240
1
12
Order By: Relevance
“…Arteriography afforded a useful serial assessment of reduction in tumor neovascularity and greatly assisted in surgical planning for either limb preservation or amputation. Our rate of limb preservation (92%) is comparable if not better than others reported in the literature [1,3]. Two patients had local recurrence at a rate of 3.7%.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Arteriography afforded a useful serial assessment of reduction in tumor neovascularity and greatly assisted in surgical planning for either limb preservation or amputation. Our rate of limb preservation (92%) is comparable if not better than others reported in the literature [1,3]. Two patients had local recurrence at a rate of 3.7%.…”
Section: Discussionsupporting
confidence: 84%
“…By using serial arteriography to monitor tumor response and individualize the duration of neoadjuvant therapy, we achieved a 77% rate of good histologic response. We deduce that our high rate of good response likely translated into an exceptional survival rate as opposed to more traditional protocols which prescribe a set number of preoperative cycles and result in survival rates in the 70% range [1,3,4,7,19,21,24,[42][43][44]52].…”
Section: Discussionmentioning
confidence: 99%
“…At least 1 surgical complication was reported in approximately 55% of patients in some studies, although the majority were the result of the technical procedures. 1 Minor surgical complications were noted in 12 patients in the current study whereas aseptical loosening was reported to occur in 3 patients (14%), none of whom required the removal of the prosthesis. The rate of complications requiring intervention was 23% in the COSS-82 study.…”
Section: Discussionmentioning
confidence: 85%
“…At the time of last follow-up, we had not encountered any fatal doxorubicin-induced cardiotoxicity compared with other studies. 1 Cardiac failure had not been reported in any of the current study patients because the cumulative dose of doxorubicin had not exceeded 300 mg/m 2 at the time of last-follow-up. No patient had died of treatment-related complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation